Critique of Law in a Martial Arts Thriller: the Peril of Emotions, Limits of Rationality, and Pluralistic Laws - Janny H.C. Leung (Law Text Culture, 2014)
This paper explores the cinematic treatment of a cluster of themes – law, justice, morality, human emotions and social relationships – in what appears in genre to be a fairly straightforward Chinese martial arts film, Wu Xia (2011). The film is atypical for its genre, however, both in the characters it depicts and in the narrative it constructs. In particular, Wu Xia has only three fight scenes and is heavy with dialogue (both in the broad, conversational sense of spoken dialogue and in the more technical, Bakhtinian sense of dialogism (1992)). In a striking departure from genre conventions, the film develops what amounts to a cinematic commentary on jurisprudential debates about free will, punishment and ways of attributing responsibility and blame for human behaviour (for legal discussion of these issues, see Rawls 1999). Taking Bordwell (1989)’s approach to interpreting filmic meaning as exemplary in its attention simultaneously to conventional form, distinctive rhetorical styles, and historicity, I will offer an analysis of what might be called the ‘cinematic experience of justice’, a reading of Wu Xia that is especially concerned with interconnections between the film’s formal characteristics, its stated and implied meanings, and its likely impact on specific cinema audiences. Focusing on the film’s distribution simultaneously in two different Chinese language versions, one released in Hong Kong and the other throughout mainland China, the analysis compares significant language choices made in the film’s soundtrack and relates them to the respective social, political and historical contexts of film’s distribution in its two different cuts. This paper suggests that Wu Xia is highly distinctive in several ways: in how it depicts the practice of law as being starkly at odds with the emotional experience of being human; in how little faith it expresses in the rule of law; and, perhaps most significantly, in its open ridiculing of a formalistic approach to justice. I will conclude by discussing the significance of these aspects of the film in the political dynamics of China and postcolonial Hong Kong.